PEMBUATAN SISTEM INFORMASI GEOGRAFIS KESESUAIAN LAHAN TANAMAN TEBU BERBASIS WEB DI KABUPATEN MERAUKE - - Marwato; Danang Surya Candra (Indonesian National Institute of Aeronautics and Space (LAPAN), 2007)
This research is aims to have develop land resource information system for a spatial management and land use allocation by commudity development based on web and land suitable evaluation for sugar cane in Merauke Regency, Papua Province. The method which is used to organized land resource information system in development of area commudity (sugar cane) is automatization evaluation land suitability is to detect potency area of sugar cane with combined remote sensing technology and information technology based on web. The result of the evaluation land suitability for sugar cane in Merauke Regency, for the most extremely suitable land (S1) are Kl9maam Island (19,3291 hectare), Merauke (11,550 hectare), Kurik (7,746 hectare) and Semangga (524 hectare).